2005
DOI: 10.1562/2004-12-01-ra-389
|View full text |Cite
|
Sign up to set email alerts
|

Novel water-soluble bacteriochlorophyll derivatives for vascular-targeted photodynamic therapy: synthesis, solubility, phototoxicity, and the effect of serum proteins

Abstract: New negatively charged water-soluble bacteriochlorophyll (Bchl) derivatives were developed in our laboratory for vascular-targeted photodynamic therapy (VTP). Here we focused on the synthesis, characterization and interaction of the new candidates with serum proteins and particularly on the effect of serum albumin on the photocytotoxicity of WST11, a representative compound of the new derivatives. Using several approaches, we found that aminolysis of the isocyclic ring with negatively charged residues markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 37 publications
1
59
1
Order By: Relevance
“…WST11 was prepared from WST9 as described previously. 43 NPe6 was provided by Prof. Kevin M. Smith, Louisiana State University. MEM-Eagle α modification, (M0894) and HO33342 (B2261) were provided by Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…WST11 was prepared from WST9 as described previously. 43 NPe6 was provided by Prof. Kevin M. Smith, Louisiana State University. MEM-Eagle α modification, (M0894) and HO33342 (B2261) were provided by Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrophobic PSs are more likely to bind to the low-density lipoproteins (LDL), while more hydrophilic ones bind albumin fractions (Bonneau and Vever-Bizet 2008). For example, it was found that bacteriochlorophyll derivatives with improved amphiphilic properties had an increased affinity to serum albumin, and this was shown to be beneficial for the vascular targeted PDT (Brandis et al 2005). Asymmetric and amphiphilic PSs can be associated with both albumin and high-density lipoproteins (HDL) (Bonneau and Vever-Bizet 2008).…”
Section: Ps Distributionmentioning
confidence: 99%
“…The attachment of sulfonated groups to the β-positions of a tetrapyrrolic macrocycle is an alternative method toward the generation of hydrophilic sulfonated derivatives. This approach was applied to the generation of alkylsulfonated bacteriochlorins [120]. For example, sulfonated bacteriochlorophyll derivatives were prepared by reaction of Pd-bacteriopheophorbide (108) with homotaurine (Scheme 31) [120].…”
Section: Sulfonated Porphyrinsmentioning
confidence: 99%
“…This approach was applied to the generation of alkylsulfonated bacteriochlorins [120]. For example, sulfonated bacteriochlorophyll derivatives were prepared by reaction of Pd-bacteriopheophorbide (108) with homotaurine (Scheme 31) [120]. Treatment of either 109 or the sulfo-NHS ester 110 with a second equivalent of homotaurine also yielded the bis-sulfonated product 111 (with the trisulfonated compound arising from imine formation with the β-acetyl group as a minor product).…”
Section: Sulfonated Porphyrinsmentioning
confidence: 99%